The ocean engineering handbook - El-Hawary, Ferial (CRC Press, 2001)
Annotation This volume presents an up-to-date reference on cutting edge technology of all tools that support marine human activities. With articles on a broad spectrum of topics such as marine hydrodynamics and vehicle control, guidance and control systems, multi-robot cooperation, sonar systems, fiber optics in ocean engineering and models of marine vessels, the text covers important theory and practice of oceanic engineering and technology. It is designed to be used as a handbook, and contains contains over 800 equations, 100 figures and 20 tables to aid in visualization of the concepts presented. Annotation c. Book News, Inc., Portland, OR (booknews.com).
Keywords: Marine engineering -- Handbooks, manuals, etc.; Ocean engineering -- Handbooks, manuals, etc.; elektronické knihy; electronic books